Fractional resurfacing - Tannous, Zeina (2007)
Fractional resurfacing produces a distinctive thermal damage pattern by creating discrete columns of thermal damage referred to as microthermal treatment zones. It characteristically spares the tissue surrounding each microthermal treatment zone leading to fast epidermal repair. Fractional resurfacing has been successfully used in treating a variety of skin conditions including melasma, dyschromia, lentigenes, wrinkles, and acne scars with minimal downtime. It is safer to use off the face and in darker skin types.